Risks of Emerging Infectious Diseases: Evolving Threats in a Changing Area, the Mediterranean Basin. Issue 1 (24th September 2012) - Vittecoq, M.; Thomas, F.; Jourdain, E.; Moutou, F.; Renaud, F.; Gauthier‐Clerc, M.
Summary The Mediterranean basin is a biodiversity hotspot; it has historically had a large human presence that has shaped ecosystems for millennia. As the cradle of many civilizations, the area was one of the main theatres for transitions that punctuated both human and pathogen histories, which are intimately linked. Today we are living through another great historical transition summarized in the expression 'global changes'. In this context, we are witnessing a rise in the emergence of pathogens widely associated with aforementioned global changes. The Mediterranean basin might be especially vulnerable to this phenomenon due to the acute consequences global changes will have in this key intercontinental interface region. In addition, Arab revolutions and European economic crisis are creating both sanitary issues and presenting new opportunities to improve infectious disease control and prevention in the region. The aim of this review is to identify the impacts that ongoing changes might have on the risk of infectious disease emergence in the Mediterranean basin. We focussed on three key domains undergoing transformations: (i) resources, namely safe drinking water and animal products, (ii) socio‐economic factors including health inequalities within countries and poor sanitary conditions linked to ongoing conflicts and (iii) movements of people and goods that are reshaped by current changes and are intimately linked to the risk of disease proliferation. Building on recent examples, we try to identify upcoming challenges and discuss ways to meet them in the light of existing international human and veterinary health guidelines and their possible improvements.